Sosialisasi dan Edukasi Literasi Keuangan pada Masyarakat Penerima Bantuan Sosial dalam Meningkatkan Kesejahteraan Masyarakat Miskin - Supartono; Agus Anggiana; Arinda Triagita; Citra Maharani; Ellysa Shalsabella; Gian Mariana; Jamilatul Rizqiyah; Zita Andini Sabillah; Ilham Rizqi Ariyandi (CV. ITTC INDONESIA, 2024)
The study aims to analyze how the financial literacy influence of the social welfare recipients of the village of Jatiwangi RT 01 can help improve the well-being of the community in the village. Increased public literacy on finance is essential to boosting the economy and improving the well-being of individuals and families. However, people still lack understanding of financial literacy, including people in Jatiwangi Village. Therefore, there is a need for a community service program that enhances financial literacy. If government efforts to reduce poverty through social assistance programmes are not offset by increased financial awareness for those who receive aid, the results will be less satisfactory. The research is conducted through surveys, observations, and financial education to the target community directly. The results of the research show that the community of beneficiaries of social assistance in Jatiwangi Village RT 01 can be more conscious in regulating family finances as well as can maximize the use of social aid funds obtained, with the provision of education and socialization of financial literacy carried out by dedication students. Therefore, this study aims to know and understand how the process or implementation of socialization and education of financial literature to recipients of social assistance funds in Jatiwangi Village RT 01.